PENINGKATAN KUALITAS PEMBELAJARAN SENI KERAJINAN BATIK DAN CHARACTER BUILDINGDENGAN MENGGUNAKAN METODE LESSON STUDY - - Ismadi (FBS UNY, 2012)
This study aims at describing the learning process and its influence to the learning improvement and character building. The subject of this study is a group of 23 students of semester five in Craft Education Study Program of Department of Arts and Craft Education. This research is designed as an action research which adopts the resarch methods applied by Kemmis and Metaggart and is conducted in two cycles. The data collecting technique was conducted through observation, interviews, and documentation. The data were analyzed based on Descriptive Qaualitative Research method.The research results show that the learning process improves, which leads to the manifestation of character building in Batik Craft Art course. This is indicated bt the changes of the students’ attitudes and behavior in class. The students pay attention to the course materials given by the lecturer, and they also actively join the discussions held in class. From the record of students’ assessment of each competence, it shows the improvement of the students’ grades in this course.